THE INFLUENCE OF LIFESTYLE AND FINANCIAL LITERACY ON EMPLOYEE FINANCIAL MANAGEMENT - Abdul Rasyid (SEAN Institute, 2023)
This research intends to investigate the influence of lifestyle and financial literacy on employee financial management. The present study employed quantitative research methodologies to investigate the topic at hand. Surveys were conducted and data was collected through the distribution of questionnaires to a sample of employees working in micro, small, and medium enterprises (MSMEs) located in the city of Jayapura. The research sample comprised 100 participants. The data that was gathered was subjected to analysis through the utilisation of regression analysis and hypothesis testing, facilitated by the employment of SPSS tools. The version of Windows being referred to is 25.0. The findings of this study indicate that there exists a noteworthy correlation between lifestyle choices and financial literacy with regards to the management of employees' finances. The adoption of a healthy lifestyle and the attainment of a high degree of financial literacy have been observed to correlate with improved financial management practises. The ramifications of these findings have significant importance for both organisations and individuals seeking to enhance the financial well-being of their employees.